Political Competition (A theory with applications to the distribution of income) - John Roemer (University of California, Department of Economics, 1999)
The formal model of political competition almost ubiquitously employed by students of political economy is one in which political parties play no role. That model, introduced by Anthony Downs (1957) over forty years ago, portrays a competition between candidates, whose sole motivation for engaging in politics is to enjoy the power and perquisites of office holding. Although voters care about policies, the candidates do not; for them, a policy is simply an instrument to be used, opportunistically, as an entry ticket to a prosperous career. Political parties, however, have, throughout the history of democracy, cared about policies, perhaps because they are formed by interest groups of citizens. Therefore the Downsian model cannot be viewed as an historically accurate model of party competition.
Keywords: 330